ADE: Autonomous DEcision making in Very Long Traverses - Ocón, J; Dragomir, I; Coles, A; Green, A; Kunze, L; Marc, R; Perez, CJ; Germa, T; Bissonnette, V; Scalise, G; Foughali, M; Kapellos, K; et al. (Lunar and Planetary Institute, 2020)
ADE (Autonomous DEcision making in Very Long Traverses) is an ongoing H2020 project aiming to develop key technologies for future space robotics missions. The focus of the project is to develop an exhaustive autonomous system for planetary rover exploration that can traverse at least 1km/sol, perform and maximize the scientific data collection, take appropriate decisions in nominal and contingency situations and ensure its safety at any moment. In this paper we describe the system developed and its capabilities, along with the validation approach and testing facilities.